Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pada Toko Ac Daya Teknik Di Kota Depok - Shendy Sulaeman; Wawan Supriyatna (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The purpose of this study was to determine the effect of Service Quality and Price on Customer Satisfaction at the Daya Teknik AC Store in Depok City, both partially and simultaneously. The method used is quantitative. The sampling technique uses simple random sampling technique, the sample in this study amounted to 69 respondents. Data analysis uses validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis test. The results of this study are that Service Quality affects Customer Satisfaction with the regression equation Y = 11.892 + 0.338 X1. Hypothesis testing obtained a calculated t value> t table or (4.375> 1.996) This is also reinforced by the sig value. <sig.0.000 or (0.000 <0.050). Thus, Ho1 is rejected and Ha1 is accepted, this shows that partially there is a positive and significant influence between Service Quality and Customer Satisfaction at the Daya Teknik AC Store in Depok City. Price affects Customer Satisfaction with the regression equation Y = 35.235 + 0.295 X2. Hypothesis testing obtained a value of t> calculated t table or (2.884> 1.996) this is also reinforced by the sig. < sig.0.005 or (0.005 < 0.050). Thus, Ho2 is rejected and Ha2 is accepted, this shows that partially there is a positive and significant influence between Price on Customer Satisfaction at the Daya Teknik AC Store in Depok City. Service Quality and Price affect Customer Satisfaction with the regression equation Y 19.701 + 0.290 X1 0.174 X2. Hypothesis testing obtained a value of F count> F table or (11.363> 2.750), this is also reinforced by the sig. < sig. 0.000 or (0.000 < 0.050). Thus, Ho3 is rejected and Ha3 is accepted, this shows that simultaneously there is a positive and significant influence between Service Quality and Price together on Customer Satisfaction at the Daya Teknik AC Store in Depok City.